Indian Islamic Architecture Forms and Typologies, Sites and Monuments - Burton-Page, John (Brill, 2007)
The British scholar John Burton-Page contributed numerous formative articles on Indian Islamic architecture for the Encyclopaedia of Islam over a period of 25 years. Assembled here for the first time, these offer an insightful overview of the subject, ranging from the earliest mosques and tombs erected by the Delhi sultans in the 13th, 14th and 15th centuries, to the great monuments of the Mughal emperors dating from the 16th and 17th centuries. The articles cover the principal forms of Indian Islamic architecture -- mosques, tombs, minarets, forts, gateways and water structures -- as well as the most important sites and their monuments. Unsurpassed for their compression of information, these succinct articles serve as the best possible introduction to the subject, indispensible for both students and travellers. The articles are supplemented by a portfolio of photographs especially selected for the volume, as well as a glossary and up to date bibliography.